1877 Colo. Sess. Laws 304 - (:unkn) unknown (My University, 1877)
§ 154: Prohibited the carrying with intent to assault another any pistol, gun, knife, dirk, bludgeon, or other offensive weapon.
Keywords: CARRY - INTENT TO COMMIT CRIME